(untitled) (Research, Society and Development, 2026)
This study aimed to analyze scientific evidence on the effects of resistance training on physical health and quality of life in postmenopausal women. This is an integrative literature review with a quantitative approach, conducted in the PubMed and Virtual Health Library (BVS) databases. Studies published between 2015 and 2026, available in full text, in Portuguese, English, and Spanish, and involving resistance training interventions in this population were included. Eight studies were selected for analysis. Overall, the findings indicate that resistance training contributes to increased muscle strength, improved body composition — with higher lean mass and reduced body fat — as well as benefits in bone mineral density and metabolic indicators. Improvements in functional capacity and quality of life were also observed, especially in short-term interventions. It is concluded that resistance training is an effective strategy for promoting health in postmenopausal women, and continued practice is essential to maintain these benefits.